The role of mite pocket-like structures on Agama caudospinosa (Agamidae) infested by Pterygosoma livingstonei sp. n. (Acari: Prostigmata: Pterygosomatidae) - Bertrand, Michel; Modrý, David (Folia parasitologica, 2004)
Pterygosoma livingstonei sp. n. collected from the Kenyan lizard Agama caudospinosa Meek shows morphological affinities with other South African congener species parasitizing lizards of the genus Agama, especially with P. triangulare Lawrence, 1936, but it differs in having glabrous genua II and III. P. livingstonei shows affinities with the Lawrence's hispida species group in the characters of genital and peripheral setae. This new species was found concentrated in a nuchal "mite pocket-like structure", a behaviour previously unreported among species belonging to the genus Pterygosoma. Mite pockets (or acarodomatia, acarinaria) of lizards typically house damaging chigger mites, and are usually interpreted as the evolutionary host's response to limit damage caused by parasites. Because scale mites are permanent ectoparasites and less damaging than seasonally occurring larval trombiculids, the heavy infestation by P. livingstonei in the nuchal skin folds of its host is interpreted as a consequence of the best utilisation of an available protected site by these mites that spend their entire life cycle on their host and whose primitive body shape prevents them from seeking shelter beneath the scales of their lizard host.
Keywords: zvířata; Animals; Female; Host-Parasite Interactions; Lizards; interakce hostitele a parazita; ještěři; Kenya; Keňa; roztoči; ženské pohlaví; Skin; Mites; kůže